Use of Differential Equations in Population Growth Analysis - Sah, Sarswati Kumari; Sahani, Suresh Kumar (Darul Yasin Al Sys, 2024)
In this assignment we discussed differential equation applications in real-world scenarios. Differential equations are a significant area of mathematics with applications in many fields, including engineering, astronomy, biology, chemistry, physics, economics, and finance. Differential equations are used in economics to explain many concepts such as restricted and infinite growth, equilibrium and stability, and the dynamics of supply and demand in an economy. Differential equations will be used to examine several facets of Nepal in this research assignment.